1977
DOI: 10.1159/000225236
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Neoplasms in Mice Produced with Six Injections of 1,2-Dimethylhydrazine

Abstract: A highly effective but reduced injection schedule for the induction of the colon cancer in CF1 female mice is reported using 6 subcutaneous inoculations of 1,2-dimethylhydrazine at a dose level of 20 mg/kg body weight. Between the 20th and 45th week of the experiment, 83 % of the animals were tumor-bearing with a frequency of 2.1 colonic neoplasms macroscopically visible per mouse. Tumors were isolated in nature and primarily located in the distal large bowel. Some degree of carpeting of the colonic mucosa and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…DMH was used to induce colonic tumours in wild‐type, heterozygous K‐ ras tm Δ4 A /+ and homozygous K‐ ras tm Δ4 A / tm Δ4 A mice. Although activating K‐ ras mutations have sometimes been detected in DMH‐induced bowel tumours in the rat model 25, they were not detected in colonic adenomas in mouse models investigated here or elsewhere 26–28. K‐ ras tm Δ4 A / tm Δ4 A mice exhibit normal life expectancy and an overall similar spontaneous tumour incidence to that of wild‐type mice 16, indicating that K‐ ras tm Δ4 A / tm Δ4 A mice provide an excellent experimental model to explore the effects of K‐ ras 4A and 4B isoforms on colonic tumourigenesis.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…DMH was used to induce colonic tumours in wild‐type, heterozygous K‐ ras tm Δ4 A /+ and homozygous K‐ ras tm Δ4 A / tm Δ4 A mice. Although activating K‐ ras mutations have sometimes been detected in DMH‐induced bowel tumours in the rat model 25, they were not detected in colonic adenomas in mouse models investigated here or elsewhere 26–28. K‐ ras tm Δ4 A / tm Δ4 A mice exhibit normal life expectancy and an overall similar spontaneous tumour incidence to that of wild‐type mice 16, indicating that K‐ ras tm Δ4 A / tm Δ4 A mice provide an excellent experimental model to explore the effects of K‐ ras 4A and 4B isoforms on colonic tumourigenesis.…”
Section: Introductionmentioning
confidence: 76%
“…DMH·2HCl (2.0 mg/ml) was dissolved in 0.90% saline containing 1 m M EDTA and 10 m M sodium citrate, and the pH was adjusted to 6.5 using 0.5 M NaOH. Previously validated DMH treatments consisted of ten weekly injections of 20.0 mg/kg, starting at age 7–8 weeks (cumulative dose = 200.0 mg/kg DMH·2HCl or 145.0 mg/kg DMH) 26–28.…”
Section: Methodsmentioning
confidence: 99%
“…In the earliest published studies repetitive administration of DMH in rodents was demonstrated to induce colon tumors with pathological features similar to that seen in sporadic human disease,[2627] Later studies switched to AOM,[2830] due to practical advantages such as reproducibility, high potency, simple mode of application, excellent stability in solution, and low price. [29]…”
Section: Experimental Colon Carcinogenesis In Rodentsmentioning
confidence: 99%
“…), but for DMH‐treated mice, K‐ ras mutations in adenomas are much less common or rare, although DMH is known to induce intestinal adenoma formation by either activating Beta ‐ Catenin mutations or inactivating Apc mutations (Jackson et al . ; Deschner & Long ; Deschner et al . ; Diwan et al .…”
mentioning
confidence: 99%